The Evaluation of Groundwater Resources Value of Beijing Based on Emergy Theory - Ling Wang; Qing He (Advances in Materials Science and Engineering)
Accurate yet valid evaluation of values of groundwater resources is difficult. However, it is of an urgent need. Based on water resource system, the emergy synthesis of the ecological economics was used to make a systematic study on the assessment of the quantity of groundwater resources. Taking Beijing in 2012 as an example, the values of groundwater for residents life subsystem, the industrial subsystem, and the agricultural subsystem are 7.64, 6.00, and 3.25 billion Yuan, accounting for 45.24, 35.5, and 19.24% of the total value, respectively. The total value of the underground water accounts for 1.51% of the GDP in Beijing for that year. Meanwhile, Contribution Rate of Groundwater Resources (GWCR) in Beijing decreased in the following order: groundwater contribution rate for industry (GWCRI 4.52%), groundwater contribution rate for agriculture (GWCRA 3.24%), and groundwater contribution rate for residential life (GWCRL 0.71%). The conclusions will provide important basis for the government’s scientific decision to improve the level of comprehensive management of water resource.